How to Read Spinoza Without Pentimento: An Alternative to Strauss - Nusbaum, Jordan RJ (European Journal of Social Science Education and Research, 2025)
I critique the theological-philosophical assumptions that Leo Strauss uses to justify his controversial method of reading Baruch Spinoza, and I conclude by justifying an alternative interpretive method. Strauss’s method suggests that Spinoza’s texts intentionally contradict themselves so to couch his more controversial views in established dogma, thereby skirting the censorship of authorities. Strauss argues that reading “between the lines” allows the more astute of Spinoza’s readers to decipher an encrypted pentimento that reveals an esoteric or hidden aspect of his philosophy. Although Strauss’s method is divisive within the scholarship, Edwin Curley – a leading Spinoza translator and commentator – has, on more than one occasion, signaled his support for Strauss’s method despite expressing a sympathy with Strauss’s critics. I argue that Curley’s analysis of the issue does not fully engage the problem posed by Strauss’s elitism. I deny that Strauss and his proponents offer a viable strategy for interpreting Spinoza’s writings because they recapitulate the interpretive principles of Plato’s “philosopher-king” which Spinoza explicitly rejects in the Theological Political Treatise (TPT) through his critique of Maimonides. I argue that Spinoza’s writings should be interpreted according to the same method of biblical interpretation that he pioneers in the TPT. Accordingly, a text – whether sacred or profane – cannot be adequately interpreted on the basis of standards extrinsic to the text itself, including the unilateral judgement of the reader. But neither can a text be adequately interpreted without the judgment of the reader, as if its truth were hidden within the text itself independent of the minds that strive to interpret it. Therefore, in exactly the same way that Spinoza interprets the Bible through a socio-historical method, so also should Spinoza’s writings be interpreted through a socio-historical method that encounters and modifies the differences between author, text, and reader through a logic that is common to all three and private to none.